Cover Feature: Rational Design of Superior, Coking‐Resistant, Nickel‐Based Anodes through Tailoring Interfacial Reactions for Solid Oxide Fuel Cells Operated on Methane Fuel (ChemSusChem 18/2018). Issue 18 (13th September 2018) - Qu, Jifa; Wang, Wei; Chen, Yubo; Li, Haidong; Zhong, Yijun; Yang, Guangming; Zhou, Wei; Shao, Zongping
Abstract : The Cover Feature shows how moderate amounts of La5.4 WO12− δ (LW) could reduce coking rate when using CH4 as fuel. This is mainly due to the beneficial phase reaction between LW and Ni–yttria‐stabilized zirconia (YSZ) anode. The synergistic effect in the new anode could remove the deposited carbon in the form of CO2 . Through a series of characterizations it was found that the excellent coking resistance is mainly due to the adsorbed water caused by WO3− x − δ . More information can be found in the Full Paper by Qu et al. onpage 3112 in Issue 18, 2018 (DOI:10.1002/cssc.201801539 ).